Cultural Communication of Didong Jalu in Takengon, Central Aceh Regency - Afriadi, Putra; Florentinus, Totok Sumaryanto; Wadiyo, Wadiyo (Catharsis, 2018)
Didong Jalu is a traditional art from Aceh Tengah (central aceh) that performs 2 (two) Didong group in one performance. Didong Jalu is an art that combines vocal and motion art with a small pillow as the property. Didong Jalu is also used as a medium of communication among societies from different ethnics. The problems of the research are (1) How is the Didong Jalu performance of Kampung Toweren societies, Takengon Central aceh Regency if it is reviewed from Entomusicology?, (2) How is Didong Jalu performance used as a medium of cultural communication by Kampung Toweren societies, Takengon, Central aceh Regency?. The research method is qualitative with interdicipline approach. The research design is case study, this research is only applicable for where the research was held. The research location is Kampung Toweren Takengon, Central aceh Regency. The research focused on Didong Jalu performance with performance concept and communication concept. The source of data was primary data involving artists, literature documents, and public figure, while the secondary data involves books, and references from previous research.the data collection techniques are observation, interview, and study document. The technique of data validity used data triangulation. Data analysis techniques consist of reduction, data presentation, data verification. The results of the research was that Didong Jalu performance observed used 2 (two) concepts, they are concept presented by Sal Murgiyanto, involving (a) beginning parts, (b) core parts, (c) final parts; (d) rhythm, (e) melody. Didong Jalu performance as a cultural communication can be seen clearly from the elements which influence communication system presented by Alo Liliweri, such as, Didong Jalu as a communicator, communicant, message, media, effect, athmosphere, and disturbance.